Distributed Functional Connectome of White Matter in Patients With Functional Dyspepsia - Xu, Qiang; Weng, Yifei; Liu, Chang; Qiu, Lianli; Yang, Yulin; Zhou, Yifei; Wang, Fangyu; Lu, Guangming; Zhang, Long Jiang; Qi, Rongfeng (Frontiers in Human Neuroscience, 2021)
Purpose: We aimed to find out the distributed functional connectome of white matter in patients with functional dyspepsia (FD). Methods: 20 patients with FD and 24 age- and gender-matched healthy controls were included into the study. The functional connectome of white matter and graph theory were used to these participants. Two sample T test was used for the detection the abnormal graph properties in FD. Pearson correlation was used for the relationship between properties and information of clinical and neuropshychological. Results: patients with FD and healthy controls showed small-world properties in functional connectome of white matter. Compared to healthy controls, the FD group showed decreased global properties(Cp, S, Eglobal, Elocal). Four pairs of fiber bundles who connected to frontal lobe, insula and thalamus were affected in FD group. Duration and Pittsburgh Sleep Quality Index (PSQI) positive correlated with the betweenness centrality of white matter ROIs. Conclusion: FD patients turned to a non-optimized functional organization of WM brain network. Frontal lobe, insula and thalamus were key regions in brain information exchange of FD. It provided some novel imaging evidences for the mechanism of FD.